Integrating seasonal climate forecasts into adaptive social protection in the Sahel. (3rd July 2021) - Daron, Joseph; Allen, Mary; Bailey, Meghan; Ciampi, Luisa; Cornforth, Rosalind; Costella, Cecilia; Fournier, Nicolas; Graham, Richard; Hall, Kathrin; Kane, Cheikh; Lele, Issa; Petty, Celia; et al.
ABSTRACT: Sahelian West Africa is a region of high year-to-year climate variability that can significantly impact on communities and livelihoods. Adaptive social protection (ASP) is being introduced in the region to support vulnerable people through enabling more effective responses to climate shocks, bridging social protection with disaster risk reduction and climate change adaptation. The ASPIRE (Adaptive Social Protection: Information for enhanced REsilience) project aimed to provide technical support to the World Bank's Sahel Adaptive Social Protection Programme through demonstrating the use of climate forecasts in ASP and promoting dialogue between climate and social protection stakeholders. Here we discuss lessons learned in the project, highlighting challenges and opportunities for including climate forecasts in early warning systems to inform ASP. We provide recommendations to help achieve ASP systems designed to use climate forecasts, arguing that tailored seasonal forecast products have potential in some countries to improve the lead time of interventions to address climate-induced disasters. Critical to this is continued investment in underpinning science and capacity building of climate and social protection stakeholders, as well as strengthened dialogue between actors to co-develop climate forecasts that provide actionable information.